Modulation of Oxidative Stress and Hyperglycemia by Rheum spiciformis in Alloxan Induced Diabetic Rats and Characterization of Isolated Compound - Bhat, Aashiq Hussain; Dar, Khalid Bashir; Zargar, Mohammad Afzal; Masood, Akbar; Ganie, Showkat Ahmad (Drug Research, 2019)
This study evaluates the ameliorative potential of Rheum spiciformis methanolic (RS-MeOH) extract in reducing oxidative stress and hyperglycemia in albino rats along with characterization of possible therapeutic compound(s). Groups treated with 50 and 100 mg/kg bw plant extract (RS-MeOH ) decrease blood glucose levels from 359.9±8.2 to 209.5±8.5 mg/dl (50 mg/kg bw) and 354.7±13.3 to 162.5±7.4 mg/dl (100 mg/kg bw) on the 0th and 14th day (P<0.001) respectively. This reduction in blood glucose was significant as compared to glibenclamide (20 mg/dl) which reduced glucose levels from 297.7±11.39 to 132.9±8.74 mg/dl on 0th and 14th day respectively. Biochemical parameters triglycerdies, cholesterol, low density lipoprotein (LDL) and creatinine were also reduced in a dose dependent manner. Liver marker enzymes were positively modulated by administration of RS-MeOH (P<0.001). Antioxidant enzyme profile showed an enhanced/better pattern after the administration of RS-MeOH extracts for reduced glutathione, reduced glutathione (GR), glutathione peroxidase (GPx), glutathione–S-transferase (GST) and superoxide dismutase (SOD) in both liver and pancreas. Moreover pancreatic histopathology reports revealed β-cell restorative effects with RS-MeOH, thereby potentiating its role in improving blood glucose levels. RS-MeOH purification and isolation studies involving GC-MS and NMR techniques revealed presence of emodin type compounds in RS-MeOH. Overall Rheum spiciformis showed ameliorative action on oxidative stress and hyperglycemia, however further studies to explore the mechanism of action of possible therapeutic compound in invivo clinical trials will prove beneficial for the advancement of new oral antidiabetic drug.
Keywords: Anti-hyperglycemic; oxidative stress; GC-MS; NMR; Glutathione, antioxidant enzymes